Hygienic-Sanitary and Good Manufacturing Evaluation of Chicken Cuts Marketed In Chókwè City - Massingue Junior, Abel; Sigauque, Francisco José Luís; Machalela, Angélica Agostinho; José, António Elísio; Nanelo, Rafael Francisco (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study assessed the hygiene and health conditions of chicken cuts sold in Chókwè city. The checklist method was applied following Resolution RDC No. 216/04 to assess the hygiene and health conditions, verifying the adequacy or otherwise of the items evaluated. When the checklist was completed, the following was considered: (C) "Compliant" - commercial establishments that met a specific requirement, (NC) "Non-Compliant" - commercial establishments that did not comply with the observed requirement and (NA) "Not Applicable" for the requirement that was not met by the establishments surveyed. The results showed that the highest levels of compliance (20 to 100%) were found for the items building, facilities, equipment, furniture and utensils, sanitization of facilities, equipment, furniture and utensils, control of vectors and urban pests, water supply, waste management, handlers, raw materials and packaging, storage/preservation, display of meat except for documentation and registration. It can, therefore, be concluded that the establishments comply with good manufacturing practices. Contribution to Sustainable Development Goals (SDGs)SDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 8: Decent Work and Economic Growth SDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land